Influence of cenospheres and fly ash on the mechanical and durability properties of high-performance cement mortar under different curing regimes. (12th April 2021) - Danish, Aamar; Mosaberpanah, Mohammad Ali
Highlights: Fly ash and CS (two different sizes) were used to prepare high-performance mortar. Prepared specimens were evaluated at different curing temperatures and conditions. Mechanical and durability properties of prepared specimens were studied. Water curing at higher temperature enhanced the properties of prepared specimens. Incorporation of CS (10-15%) improved the properties of prepared specimens. Abstract: Due to increased urbanization and population in conjunction with growth in the economy, the construction industry is expanding rapidly. The expansion of the construction industry has increased the consumption of concrete and its constituents, especially Ordinary Portland Cement (OPC). The increased production and consumption of OPC is increasing environmental pollution due to the exponential increase in greenhouse gas emissions (like carbon dioxide). Because of this, incorporation of supplementary cementitious materials (SCMs) (like fly ash, silica fume, and slag) as cement replacement is encouraged to reduce the overall detrimental impact on the environment and promote sustainability in the construction industry. In this study, Cenosphere (CS) and Fly Ash (FA) were used as 0, 5, 10, 15, and 20% by mass replacement of OPC to prepare high-performance mortar. The effect of CS-FA modified high-performance mortar evaluated for mechanical and durability properties cured with different conditions (water and dry) and temperatures (20 °C and 80 °C). The properties studied included workability, packing density, water absorption, compressive strength, flexural strength, fire resistance, acid attack, and drying shrinkage. The results revealed that water curing at a higher temperature is effective than other curing condition and temperature. It was also indicated that the incorporation of CS (10–15%) gives better results for properties like flexural strength, fire resistance, acid attack, and water absorption.